La desorganización familiar y el consumo de alcohol en adolescentes en la Unidad Educativa "Once de Noviembre" - Bejarano Llagua, Helen Dennisse (2021)
This research project aimed to relate family disorganization and alcohol consumption in eighth, ninth, and tenth year EGB students from "Once de Noviembre" Educational Unit. Family disorganization is a social problem that hinders relationships between family members. It has been identified that alcohol consumption in students is accompanied by the lack of attention, communication, and relationship that exists in the family nucleus. The methodology used in the execution of the research project was a non-experimental, cross-sectional, field, and bibliographic design. Due to the descriptive and correlational level, the population was made up of 544 eighth, ninth and tenth-year-old students. Their sampling was non-probabilistic and intentional. The techniques were the survey and the psychometric test. The evaluation instruments were the questionnaire and the Mast Test, through the SPSS, a Pearson correlation of 0.646 ** and a bilateral significance of 0.000 between the study variables. It was concluded that family disorganization is generated more by the lack of communication which affects coexistence. It generated that students every time they have a problem of any kind, they consume alcoholic beverages as an escape or solution to their problems, which on several occasions leads to vice, since they will not stop drinking and thus affect their personal, social, and emotional development.